2000
DOI: 10.1136/bmj.321.7258.405
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycaemia with macrovascular and microvascular complications of type 2 diabetes (UKPDS 35): prospective observational study

Abstract: Objective To determine the relation between exposure to glycaemia over time and the risk of macrovascular or microvascular complications in patients with type 2 diabetes. Design Prospective observational study. Setting 23 hospital based clinics in England, Scotland, and Northern Ireland. Participants 4585 white, Asian Indian, and Afro-Caribbean UKPDS patients, whether randomised or not to treatment, were included in analyses of incidence; of these, 3642 were included in analyses of relative risk. Outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

157
5,041
31
306

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,712 publications
(5,535 citation statements)
references
References 39 publications
157
5,041
31
306
Order By: Relevance
“…These results are broadly in line with the less‐certain effects seen in major randomized trials, and they support the conclusion that improved glycaemic control reduces CV events 6, 17, 18. Participants were newly started on insulin and generally achieved and maintained reasonable glycaemic control during follow‐up in the study, with median HbA1c of 9.3% (78 mmol/mol) at baseline, declining to 7.4% (57 mmol/mol) at the end of year 1 and 7.3% (56 mmol/mol) at the end of year 4.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are broadly in line with the less‐certain effects seen in major randomized trials, and they support the conclusion that improved glycaemic control reduces CV events 6, 17, 18. Participants were newly started on insulin and generally achieved and maintained reasonable glycaemic control during follow‐up in the study, with median HbA1c of 9.3% (78 mmol/mol) at baseline, declining to 7.4% (57 mmol/mol) at the end of year 1 and 7.3% (56 mmol/mol) at the end of year 4.…”
Section: Discussionsupporting
confidence: 80%
“…The ADVANCE study saw a 6% non‐significant reduction in MACE events associated with a 0.8% reduction in HbA1c 4. The relationship between HbA1c reduction and CV events in the UKPDS was also suggestive, but uncertain at study end, but again significant at the end of the extension phase (MI, all‐cause mortality), and in study observational analysis 17, 19, 22. Accordingly, the meta‐analyses of these studies also found statistically significant reductions in MI and overall CV events 18, 23.…”
Section: Discussionmentioning
confidence: 96%
“…However, higher HbA 1c was a strong risk factor for sudden death, whereas no association was found between baseline HbA 1c and risks of fatal or nonfatal MI and heart failure death 33. Although the effect of tight glycemic control on microvascular complications has been well established,5, 28, 31, 34 its effect on macrovascular complications remains controversial, and more research is warranted to further study these relationships in patients on hemodialysis with DM. In this study we observed only moderate associations between higher HbA 1c and increased rates of cardiovascular mortality and MI.…”
Section: Discussionmentioning
confidence: 99%
“…Each 1% of mean HbA1c reduction has been associated with a 21% reduction in risk of any diabetes‐related complication 1. In general, a target HbA1c level of <53 mmol/mol (<7%) is optimal, according to diabetes guidelines 2…”
Section: Introductionmentioning
confidence: 99%